Nitrate removal from groundwater using a reactive stream stabilization structure - Mitchell, Christina M., author; Carlson, Kenneth, advisor; Watson, Chester, committee member; Stromberger, Mary, committee member (Colorado State University. Libraries, 2010)
Riparian zones that remove nitrate (NO3-) from groundwater play a significant role in protecting and improving the quality of receiving surface waters. Denitrification, the microbial conversion of NO3 to gaseous forms of nitrogen (N ) is an important removal mechanism in these systems. For this process to occur there must be a supply of organic carbon (C ). High levels of organic C may be found in the subsurface of relatively undisturbed riparian zones. However, in areas where streambank erosion has resulted in the loss of riparian vegetation (C source) and organic-rich sediments, the amount of C available for denitrification is likely to be low. Vegetation may become established in these areas soon after the banks are stabilized using standard structural and/or bioengineering techniques. However, it will take time for organic C to accumulate in the soil. Thus, significant NO3 removal via denitrification will not be immediately observed following the completion of bank stabilization work. This study examined the potential for improving existing streambank stabilization designs to accelerate and maximize groundwater NO3 removal benefits. A simple, cost-effective structure, called the reactive stream stabilization (R S 2) structure, was designed for the purpose of this study. The RS2 structure combines a permeable reactive barrier composed of solid-phase organic C (sawdust) with a common bank stabilization technique (longitudinal peaked stone toe protection). A small field-scale RS2 structure and a control (no organic C amendment) were constructed along a stream in July 2003. The two systems were monitored from August to December 2003 and from M ay to September 2004. During the initial monitoring period, N O 3 removal in the reactive barrier averaged 93% (7.27 mg N L-1 along the upslope edge, versus 0.48 mg N L"' along the downslope edge). In comparison, NO3 removal in the control averaged 30% (12.3 mg N L-1 along the upslope edge, versus 8.65 mg N L-1 along the downslope edge). It was not possible to measure NO3 removal in the control the following spring and summer because the artificially generated plume of NO3 was not intercepted by the monitoring wells in the system. The plume was, however, intercepted by the wells located in the reactive barrier. Nitrate loss in the reactive barrier was high and averaged 97% (17.9 mg N L-1 along the upslope edge, versus 0.51 mg N L-1 along the downslope edge) during this period. The results of this study suggest that RS2 structures can enhance groundwater NO3 removal along streams. Additional field testing needs to be completed to verify these results, but it appears that the RS2 structure could be an effective tool for reducing NO3 loading to waterways.
Covers not scanned.
Keywords: Nitrates; Groundwater -- Pollution; Groundwater -- Purification